The Effect of Addition of Tolo Bean Flour on Organoleptic Properties, Nutritional Value, and Acceptability of Pumpkin Steamed Sponge (Lakulo) as an Alternative Snack for Anemic Adolescents - Made Darawati; Ellisabeth Mellisa D; Abdul Salam; I Gde Narda Widiada; Niketut Sri Suledri; Irianto Irianto (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. Teenage girls are prone to anemia because they are at reproductive age and need three times more iron daily than young men. Anemia in adolescents can cause a decrease in body immunity, concentration, fitness, and productivity. One of the efforts that can be made to contribute to the prevention of anemia is to provide local food-based high protein and Fe snacks, namely by adding tolo bean flour to the pumpkin steamed cake. The resulting sponge contains an excellent nutritional value so that it can be an alternative snack for teenagers with anemia. Research Methods. This research was conducted at the Food Technology Science Laboratory (ITP) of the Mataram Health Polytechnic of the Indonesian Ministry of Health in August 2021. The analysis of the nutritional content of Bolu Kukus Lakulo was conducted at the Analytical Chemistry Laboratory, Mathematics and Natural Sciences Faculty, Mataram University, and the Health Testing and Calibration Laboratory. The consumer acceptance test was conducted at SMAN 9 Mataram. This study used an experimental method with a completely randomized design (CRD). The data collected is on organoleptic properties, nutritional value, and acceptability. The processing method uses descriptive statistical analysis and one-way ANOVA at a confidence level of 95% or alpha 0.05. Research Result. Based on the ANOVA test, it was found that the addition of tolo bean flour had a significant effect on the aroma, texture, and taste of the lactulose-steamed sponge p<0.05. Based on the organoleptic test, treatment t4 (addition of 20% tolo bean flour) was the preferred treatment level by the panelists. The results of the proximate test of Laculo steamed cake with the best treatment had a water content of 43.5%, ash content of 0.90%, fat content of 13, 2%, 7.11% protein content, 35.3% carbohydrates, 17.6 mg Fe content.  Conclusion. An acceptance test was carried out on 30 young women by giving 100 grams of Laculo steamed cake and showed that 27 people (90%) belonged to good acceptance and three people (10%) belonged to poor acceptance.